PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PADA PENGGUNA APLIKASI GOJEK DI KOTA BATAM - Widyasari, Helen; Suhardi, Suhardi (SCIENTIA JOURNAL, 2021)
The direction of this study is to ensure the results of product quality and service quality on customer satisfaction. using purposive sampling technique with a sample size of 100 respondents. Methods of data collection by distributing questionnaires. Testing data quality in the study used validity and reliability tests, classical assumption tests and test the effects of a study using multiple linear regression analysis and analysis of the coefficient of determination, to test the study hypothesis using the t and F tests, the test using the software version of SPSS 25. The coefficient of determination (R2) obtained from the variable product quality and service quality have an effect on 78.2% of customer satisfaction. The result of multiple linear regression test shows that product quality has an effect of 74.3% on customer satisfaction and service quality has an effect of 31.1% on customer satisfaction. Based on the results of the t test and F test, it can be concluded that product quality and service quality partially have a significant effect on customer satisfaction and product quality and service quality simultaneously have a significant effect on customer satisfaction of Gojek application users.